The obligation of companies to pay Zakat in Malaysia: a re-examination of the maelstrom of legal issues - Oseni, Umar Aimhanosi; Ariff Abdul Ghadas, Zuhairah (2013)
Since the emergence of the principle of separate legal entity in modern company law as established in the locus classicus of Salomon v. A. Salomon & Co. Ltd. (1897) AC 22, a number of Islamic-related studies have been carried out to justify the recognition of similar entities in the classical Islamic law. As much as this notion would look benign, it has touched off a maelstrom of controversy among the contemporary Muslim jurists. There is no doubt that the rulings of the National Fatwa Committee and the Selangor Fatwa Committee are in consonance with that of the Islamic Fiqh Academy of the Organisation for Islamic Cooperation (OIC) which provides that the company is obliged to pay zakat either on behalf of its shareholders or itself. The Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) also has its relevant Financial Accounting Standards for calculating the amount of zakat to be paid by Islamic financial institutions which are undeniably legal entities. This has been disputed based on cogent reasons which seek to examine the religiosity of a legal entity. This controversy is the crux of this paper, which revisits the issue of the (non)obligation of companies to pay zakat under the Malaysian legal and regulatory policies. While acknowledging previous studies on this subject by a learned jurist, which up till now, has remained unchallenged, this paper takes a step further to argue that considering the legal complexities involved from both the Sharī‘ah and Malaysian law, there should be some other mandatory CSR requirements for all companies regardless of whether their businesses are Sharī‘ah-compliant or not. For this purpose, the study classifies the companies in Malaysia into two: first, normal companies without any Sharī‘ah requirements, and second, Sharī‘ah-compliant companies such as Islamic financial institutions. Individual shareholders should be required to pay their zakat by themselves based on their respective dividends at the end of the financial year. The paper concludes that emotions apart, this puzzle cannot be resolved if the decision-makers are not well grounded in the dynamics of the secular legal system under which such Sharī‘ah regime operates.